2017
DOI: 10.5709/acp-0222-2
|View full text |Cite
|
Sign up to set email alerts
|

Trypophobic Discomfort is Spatial-Frequency Dependent

Abstract: Clusters of holes, such as those in a lotus seedpod, induce trypophobic discomfort. Previous research has demonstrated that high-contrast energy at midrange spatial frequencies in images causes trypophobic discomfort. The present study examined the effects on discomfort of eliminating various spatial frequency components from the images to reveal how each spatial frequency contributes to the discomfort. Experiment 1 showed that eliminating midrange spatial frequencies did not affect trypophobic discomfort, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 24 publications
6
54
0
Order By: Relevance
“…experience of the objects. Actually, low-pass filtered images of trypophobic objects are sufficient to induce trypophobic discomfort (Sasaki et al, 2017) and this previous finding supports our notion about unconscious emotional processing of trypophobic objects.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…experience of the objects. Actually, low-pass filtered images of trypophobic objects are sufficient to induce trypophobic discomfort (Sasaki et al, 2017) and this previous finding supports our notion about unconscious emotional processing of trypophobic objects.…”
Section: Discussionsupporting
confidence: 88%
“…Although subsequent studies have shown that trypophobia does not only involve the middle spatial frequency (Le et al, 2015;Sasaki et al, 2017), excess energy at the midrange spatial frequency possibly contributes to unconscious emotional processing of trypophobic images. To confirm this possibility, we conducted a similar spectrum analysis to that of Cole and Wilkins (2013).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Two main theoretical frameworks have been proposed to explain trypophobia (Cole & Wilkins, 2013;Kupfer & Le, 2017;; both theories suggest that the visual discomfort elicited by trypophobic stimuli is an evolved response to help organisms detect and avoid harmful stimuli. One proposal is that the characteristic trypophobic patterns contain excessive energy at mid-range spatial frequencies, as defined in previous work (Sasaki et al 2017: 2-9 cycles per degree of visual angle (cpd); Fernandez & Wilkins 2008: 3 cpd +/-2 octaves). This same spectral energy profile can also be observed in the patterning of many venomous and/or predatory animals like snakes and spiders (Cole & Wilkins, 2013).…”
Section: Introductionmentioning
confidence: 99%